Classical Fourier analysis via mild distributions (Nonlinear Studies, 2019)
It is the purpose of this article to point out that the setting of mild distributions, which is based on the use of the special Segal algebra $\SORd$, also provides useful insight for various questions of classical Fourier analysis.The concrete topics to be treated are: Summability of Fourier transforms; Generalized Fourier transform, spectrum; Representation of multipliers;